Supply chain coordination with random yield and demand uncertainty. Issue 1 (2nd January 2018) - Pal, Brojeswar; Sana, Shib Sankar; Chaudhuri, Kripasindhu
Abstract: Uncertainty is a major challenging factor in the marketing strategies of the players in a supply chain. In this study, the random yield for both the supplier and manufacturer is investigated to find the optimal decisions in the environment of demand uncertainty. To meet the effect of random yield in the supplier's production, the manufacturer places a flexible ordering policy in a range with conditions imposed thereupon. It is also assumed that the manufacturer faces both the under-stocking and over-stocking risk. In the over-stock situation, the model is developed with the chance factor of holding and selling with salvage value for the extra products. The behavior of the model under a centralized, vertical Nash approach is analysed. A manufacturer-Stackelberg and revenue sharing contract with penalty and sharing are also discussed. The sensitivity of the key parameters is examined to test the feasibility of the model. Finally, a numerical example with graphical illustrations is provided to investigate the proposed model.